IS/IT Strategic Planning for Digital Maturity Development in an FMCG Skincare Enterprise - Devi Yurisca Bernanda; Johanes Fernandes Andry; Francka Sakti Lee; Neti Amalia (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
In this study, an IS/IT strategic plan will be developed for FMCG Skincare Enterprises, a firm that operates within the oral care and personal care sector, with a high regard for innovation in its products. This research adopts a qualitative descriptive case study methodology is employed, whereby the study deliberately narrows down the scope of investigation to a single organization. Within this framework, the Ward and Peppard model is used to examine the external and internal environments of the business, in order to determine the information needs of the organization. Besides, the McFarlan Strategic Grid is applied to categorize and prioritize IS/IT initiatives in terms of their strategic importance. Based on the results, it is evident that the firm enjoys numerous competitive advantages, such as having innovative products and employing shoppertainment marketing strategies using digital technology to widen the market coverage. Nonetheless, the results also point out some strategic problems that the organization faces, such as having low production capacity and being heavily reliant on a specific digital marketing channel, TikTok Shop. This study proposes a hybrid system development strategy method as the best way to incorporate digital systems. The IS/IT strategic roadmap proposed will enable the firm to improve its digital structure, increase efficiency, and ensure that it transforms into a competitive organization in the beauty industry through time.